ALGORITMA GREEDY COLORING PADA WEBSITE ENSIKLOPEDIA PETA - Nugroho, Ibnu Aldi; Fauziah, Fauziah; Hayati, Nur (Jurnal Ilmiah Teknologi dan Rekayasa, 2024)
Graph coloring is used, because the results of graph coloring can be used in several systems, such as the scheduling and the coloring of map areas in this study. The goal in implementing graph coloring here is to get as few colors as possible in the 44 borders of villages in Jakarta Pusat. The problem of coloring graphs on the Jakarta Pusat’s villages map uses a greedy algorithm that exists on web-based maps and makes encyclopedias to support descriptions of areas that have been colored. The greedy algorithm is a form of algorithm that is currently developing in optimization problems by forming a step-by-step solution. Greedy algorithm can be applied to resolve the problem of graph coloring. The best solution to answer a graph coloring problem is to determine the chromatic number ????(????) using the greedy algorithm. Graph coloring on a map is done using a greedy algorithm to obtain the minimum number of colors possible without adjacent regions using the same color. Based on the research results, the least number of colors used in coloring the village map in Central Jakarta, which consists of 44 areas, is 6 types of colors.